2021
DOI: 10.36941/jesr-2021-0097
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Contribution of Mindfulness and Gratitude in Predicting Happiness among University Students

Abstract: The present study aims at identifying the separate and interactive contribution of gratitude and mindfulness in predicting happiness; examining the relationship between these variables; identifying differences between students with high happiness and students with low happiness in gratitude and mindfulness; and identifying the levels of gratitude, mindfulness, and happiness among the students of Princess Nourah Bint Abdulrahman University. The research sample consisted of 447 female students aged 18-25 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…A significant level value was considered when p-value -< 0.05 and a highly significant level value was considered when p-value -<0.001, While p-value >0.05 indicated nonsignificant results. (Alsukah & Basha, 2021) who performed study about" the relative contribution of mindfulness and gratitude in predicting happiness among university students" and found that there was a moderate level of mindfulness among students as they looked forward to identify their role in life and surroundings. On the contrary (Sousa et al, 2021) who conducted study about "Brief mindfulness-based training and mindfulness trait attenuate psychological stress in university students: a randomized controlled trial" and stated that individuals who have high level of trait mindfulness have low levels of stress and anxiety.…”
Section: Statistical Analysis Of Resultsmentioning
confidence: 99%
“…A significant level value was considered when p-value -< 0.05 and a highly significant level value was considered when p-value -<0.001, While p-value >0.05 indicated nonsignificant results. (Alsukah & Basha, 2021) who performed study about" the relative contribution of mindfulness and gratitude in predicting happiness among university students" and found that there was a moderate level of mindfulness among students as they looked forward to identify their role in life and surroundings. On the contrary (Sousa et al, 2021) who conducted study about "Brief mindfulness-based training and mindfulness trait attenuate psychological stress in university students: a randomized controlled trial" and stated that individuals who have high level of trait mindfulness have low levels of stress and anxiety.…”
Section: Statistical Analysis Of Resultsmentioning
confidence: 99%